Fortifikasi Jamur Tiram Putih (Pleurotus Ostreatus) dalam Pengembangan Produk Roti Tawar - Rahmatulwasyiah, Rahmatulwasyiah; Sukainah, Andi; Lahming, Lahming (Jurnal Pendidikan Teknologi Pertanian, 2024)
Oyster mushrooms can be used as a substitute for other sources of calcium, phosphorus and iron, and can be used as a nutrient-rich food. Processing of white bread is one of the foods that is easily accepted by Indonesian people. This study aims to determine the effect of oyster mushroom fortification on the chemical and organoleptic properties of the resulting white bread. This study used an experimental methodology with a completely randomized design with three replications. The resulting normality test shows that the data is normally distributed with the Shapiro-Wilk value obtained, which is >0.05 and the homogeneity test shows a significant value, which is >0.05. The results of this study indicate that the best treatment is white bread using the addition of 25% oyster mushrooms with a moisture content of 29.02%, ash content of 2.36, protein content of 8.55%), fat content of 8.05%, carbohydrate content of 51, 99%, calcium level 3743.13 mg/kg), phosphorus level 1258.85 mg/kg), and iron level 8.83 mg/kg). The color organoleptic test value on white bread with the best treatment was the addition of 25% oyster mushrooms, the color value was 3.56%, the aroma value on white bread was 3.36%, the texture value on white bread was 3.5%, and the taste value on white bread bargain 3.54%.